DETERMINACIÓN DE PARÁMETROS DE LA CONTAMINACIÓN MICROBIANA PRESENTE EN UN ÁREA DE FABRICACIÓN DE MEDICAMENTOS ESTÉRILES A BASE DE ANTIBIÓTICOS B-LACTÁMICOS (2004)
The present work shows the determination, evaluation, and  standardization of the microbiological  generated by the elaboration of sterile medications based on the -Lactamic antibiotics in a  pharmaceutical industry. Limits of contamination are established before, during and after the liberation of the area, by means of the  microbiological analysis of the environment, surfaces, equipment,  ventilation systems and work uniforms, until reliable limits and levels of  acceptance are established for each zone of the area, to fulfill the  requirements of INVIMA (Colombian Institute of Surveillance of  Medications and Foods), the agency regulating laboratories in Colombia.  By means of the microbiological analysis of the evaluated parameters, the numbers and kinds of microorganisms present in the area were determined. A complete identification of these was achieved, and the two bacterial strains were isolated: Micrococcus kristinae and   Staphylococcus xylosus. The strain of the isolated mold was:     Aspergillus fumigatus. Finally, a program of environmental     microbiological monitoring was established including the evaluation of   all  the parameters that compose and are implicit in the area, thus    assuring and supporting its continuity with the documentation and    registers developed for the sterile area of -Lactamics antibiotics.